The Big 5 for the Practicing Cardiologist - Nichols, Emma Hitt (MD Conference Express, 2013)
Practicing cardiologists are faced with many vascular challenges on an everyday basis. This article discusses the treatment options for asymptomatic carotid artery disease, recommendations for the screening and treatment of abdominal aortic aneurysms, a 5-step approach to the diagnosis and management of claudication, risk stratification for venous thrombosis, as well as the diagnosis and management of femoral access complications.